2011
DOI: 10.1179/2042618611y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of manual physical therapy in the treatment of cervical radiculopathy: a systematic review

Abstract: Although a definitive treatment progression for treating CR has not been developed a general consensus exists within the literature that using manual therapy techniques in conjunction with therapeutic exercise is effective in regard to increasing function, as well as AROM, while decreasing levels of pain and disability. High quality RCTs featuring control groups are necessary to establish clear and effective protocols in the treatment of CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 19 publications
4
53
0
2
Order By: Relevance
“…The combination of mobilization and manipulation and physical modalities when compared with placebo, education, cervical collars, exercise, ultraviolet radiation, direct galvanic current, ultrasound, and massage was not found to produce any difference in terms of pain reduction, improvement in function, or global perceived effect in patients with acute, subacute, or chronic neck pain (57). What the findings of this systematic review imply, in line with the previous systematic review (55), is that the seemingly best combination of mobilization and manipulation is with exercise and advice and not with other physical modalities. Another systematic review comparing mobilization and manipulation techniques with exercise pointed to minimal beneficial effects of these techniques, in comparison to exercise, relevant to pain and function (58).…”
Section: Manipulation and Mobilizationsupporting
confidence: 78%
See 1 more Smart Citation
“…The combination of mobilization and manipulation and physical modalities when compared with placebo, education, cervical collars, exercise, ultraviolet radiation, direct galvanic current, ultrasound, and massage was not found to produce any difference in terms of pain reduction, improvement in function, or global perceived effect in patients with acute, subacute, or chronic neck pain (57). What the findings of this systematic review imply, in line with the previous systematic review (55), is that the seemingly best combination of mobilization and manipulation is with exercise and advice and not with other physical modalities. Another systematic review comparing mobilization and manipulation techniques with exercise pointed to minimal beneficial effects of these techniques, in comparison to exercise, relevant to pain and function (58).…”
Section: Manipulation and Mobilizationsupporting
confidence: 78%
“…A Cochrane review of 2010 revealed evidence of similar effectiveness of either cervical manipulation or cervical mobilization immediately after application in terms of pain and also provided evidence on the beneficial effects of thoracic manipulation in terms of both pain and function in combined groups of patients with neck pain (12). Another systematic review focusing on cervical radiculopathy and not on the combination of patients with neck pain with or without radicular findings suggested the effectiveness of manual therapy approaches, such as thrust and non-thrust manipulation or mobilization of cervical and/or thoracic spine combined with exercise, on favorably improving pain, ROM, function, and disability (55). Finally, a more recent systematic review focusing on studies including patients with confirmed or suspected cervical radiculopathy and not the combination of patients with neck pain with or without radicular findings supported the cautious use of high-velocity low-amplitude thrust manipulation (56).…”
Section: Manipulation and Mobilizationmentioning
confidence: 99%
“…1,2,5 Spinal manipulation and mobilization, large components of chiropractic care, have been found to provide benefit to individuals with musculoskeletal conditions, particularly low back and neck pain. [6][7][8][9][10][11] Recent methodologically rigorous studies have clarified the potential for adverse events with cervical manipulation. 12,13 Specifically, current evidence suggests that individuals receiving chiropractic care do not have an excess risk of vertebrobasilar artery stroke compared to those receiving primary care.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] Furthermore, the manual physiotherapy regimen utilized in the current study, CPA, has previously been shown effective in disrupting adhesions, decreasing pain, and improving the overall quality of life in patients with recurrent SBO. [34][35][36][37] CPA integrates techniques from an array of manual modalities to optimize individualized treatment, focusing intently on the patient's specific areas of restriction.…”
Section: Discussionmentioning
confidence: 99%